Efektivitas Strategi Pencegahan Demam Berdarah Dengue Berbasis Pemberdayaan Masyarakat: Literature Review: Effectiveness of Community Empowerment-Based Dengue Hemorrhagic Fever Prevention Strategies: A Literature Review - Ricky Riyanto Iksan; Aura Permata Hikmah; Nadyana Putri; Suci Alfiana; Susiyati Amin (MPI Press, 2026)
Introduction: Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes and remains a public health problem in tropical countries, including Indonesia. The incidence of DHF tends to increase every year and has the potential to cause an Extraordinary Event (KLB). Effective prevention strategies depend not only on government intervention but also require community empowerment through active participation in Mosquito Nest Eradication (PSN) with the 3M approach (draining, covering, and burying). Objectives: This literature review aims to analyze the effectiveness of community empowerment-based dengue fever prevention strategies in reducing the risk of dengue fever incidents. Method: This study used a systematic literature review method, searching for articles through the Google Scholar database. Inclusion criteria were full-text articles published between 2020 and 2025 that discussed community-based interventions in dengue fever prevention. Result: The study results showed that community empowerment strategies through health education, mosquito larvae cadres, the National Population and Disaster Mitigation (PSN) movement, and the implementation of 3M were consistently effective in reducing mosquito larvae density and increasing community knowledge and preventive behavior. The combination of education and active community involvement proved more effective than either intervention alone. Conclution: Community empowerment-based dengue prevention strategies have proven effective in reducing the risk of dengue transmission. Increasing knowledge, changing behavior, and active community participation are key to the success of prevention programs. Therefore, strengthening education programs and cross-sectoral engagement is essential on an ongoing basis.